Therapeutic Strategy of Percutaneous Transforaminal Endoscopic Decompression for Stenosis Associated With Adult Degenerative Scoliosis. Issue 4 (May 2022) - Jin, Lin-Yu; Wang, Kun; Lv, Zhen-Dong; Su, Xin-Jin; Liu, Hai-Ying; Shen, Hong-Xing; Li, Xin-Feng
Study Design: A retrospective study. Objective: To investigate the effects of percutaneous transforaminal endoscopic decompression (PTED) for lumbar stenosis associated with adult degenerative scoliosis and to analyze the correlation between preoperative radiological parameters and postoperative surgical outcomes. Methods: Two years of retrospective data was collected from 46 patients with lumbar stenosis associated with adult degenerative scoliosis who underwent PTED. The visual analog scale (VAS), Oswestry Disability Index, and modified MacNab criteria were used to evaluate the clinical outcomes. Multiple linear regression analysis was used to analyze the correlation between radiological parameters and surgical outcomes. Results: The mean age of the 33 female and 13 male patients was 73.5 ± 8.1 years. The mean follow-up was 27.6 ± 3.5 months (range from 24 to 36). The average coronal Cobb angle was 24.5 ± 8.2°. There were better outcomes of the VAS for leg pain and Oswestry Disability Index after surgery. Based on the MacNab criteria, excellent or good outcomes were noted in 84.78% of patients. Multiple linear regression analysis showed that Cobb angle and lateral olisthy may be the predictors for low back pain. Conclusion: Transforaminal endoscopic surgery may be an effective and safe method for geriatric patients with lumbar stenosis associated with degenerative scoliosis. The predictive factors of clinical outcomes were severe Cobb angle and high degree lateral subluxation. Transforaminal endoscopic surgery may not be recommended for patients with Cobb angle larger than 30° combined with lateral subluxation.